‘Exits’ and ‘Entrances’: Roger Robinson’s Poetry between Performance and Self-promotion - Adriano Elia (Le Simplegadi)
Winner of the T. S. Eliot Prize (2019) and the Ondaatje Prize (2020), Roger Robinson takes on the role of the contemporary poet enhancing the concept of performance. Robinson’s approach to poetry involves using performative elements such as live readings, social media presence, and musical collaborations. This perspective evokes the Shakespearean motto that ‘[a]ll the world’s a stage’, where artistic and personal entrances and exits are crucial in shaping discourse. The essay considers Robinson’s activities between performance and self-promotion, focusing on the multiple performative aspects that characterise the role of the poet in the digital age.